Moderate Physical Training Ameliorates Cardiovascular Dysfunction Induced by High Fat Diet After Cessation of Training in Adult Rats - Tófolo, Laize Peron; Rinaldi, Wilson; Gôngora, Adriane Barreto; Matiusso, Camila Cristina Ianoni; Pavanello, Audrei; Malta, Ananda; de Almeida, Douglas Lopes; Ribeiro, Tatiane Aparecida; Oliveira, Anna Rebeka; Peres, Maria Natalia Chimirri; Armitage, James Andrew; Mathias, Paulo Cezar de Freitas; et al. (Frontiers in Physiology, 2019)
To test whether moderate physical training can induce long-lasting protection against cardiovascular risk factors induced by high fat diet intake after cessation of training. 90-days-old Wistar rats were submitted to a sedentary lifestyle or moderate physical training, three times a week, for 30 days. Following this, at 120 days-of age, sedentary and trained rats received a hypercaloric diet (high fat diet - HFD) or a commercial diet (NFD) for 30 days. Body weight and food intake were evaluated weekly. At 150 days-of age, hemodynamic measures (systolic, diastolic, media blood pressure, pulse pressure, pulse interval and heart rate) were made via an indwelling femoral artery catheter. Beat-to-beat data were analyzed to calculate power spectra of systolic blood pressure and pulse interval. After euthanasia, mesenteric fat pad were removed and weight and total blood was stored for later analysis of lipid profile. Consumption of a HFD increased blood pressure, pulse pressure, low frequency blood pressure variability, body weight gain, fat pad stores and induced dyslipidemia. Interestingly, prior physical training was able to partially protect against this rise in blood pressure and body fat stores. Prior physical training did not totally protect against the effects of HFD consumption but previously trained animals did demonstrate resistance to the development of cardiometabolic alterations, which illustrate, that the benefits of physical training may be partially maintained even after 30 days of detraining period.